Jakość przekładu prawniczego a cechy języka prawa - Matulewska, Aleksandra (SORUS S.C. Wydawnictwo i Drukarnia Cyfrowa, 2008)
Autorka koncentruje się na cechach języka prawa, które mają wpływ na jakość przekładu. Omówione zostają następujące cechy: archaizmy, eufemizmy, polisemia i homonimia, wulgaryzmy, metafory, faux amis, neologizmy, synonimy i quasi-synonimy, terminy o nieostrym znaczeniu, defi nicje prawne modyfi kujące znaczenie, różnice pomiędzy językiem potocznym, prawnym i prawniczym.

The author focuses on the features of the language of the law which affect the quality of translation. The following features of the language of the law are discussed: archaisms, euphemisms, polysemy and homonymy of terms vulgarisms, metaphors, false friends (faux amis), neologisms, synonyms and quasi-synonyms (also called synonymous strings), terms with vague meaning, legal defi nitions modifying the meaning, as well as the differences between colloquial language and the varieties of the language of the law.
Keywords: język prawa; przekład prawniczy; translatoryka; przekład specjalistyczny